2009
DOI: 10.1007/978-3-642-02812-0_11
|View full text |Cite
|
Sign up to set email alerts
|

Context-Aware Team Task Allocation to Support Mobile Police Surveillance

Abstract: To optimally distribute tasks within police teams during mobile surveillance, a context-aware task allocation system is designed and evaluated with end-users. This system selects and notifies appropriate team members of current incidents, based on context information (officer availability, officer proximity to the incident and incident priority) and decision rules. Eight teams of three experienced police officers evaluated this system in a surveillance task through a virtual environment, comparing it to a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…As earlier research has shown, providing such advice on which team member can best handle a certain incident benefits task performance (Streefkerk et al, 2009).…”
Section: Task Allocation In Police Surveillancementioning
confidence: 97%
See 4 more Smart Citations
“…As earlier research has shown, providing such advice on which team member can best handle a certain incident benefits task performance (Streefkerk et al, 2009).…”
Section: Task Allocation In Police Surveillancementioning
confidence: 97%
“…These claims form testable hypotheses about the expected costs and benefits of our proposed design solution. The claimed benefits of automated task allocation are faster response time and handling time of incidents, more efficient distribution of workload among team members and fewer decision errors (Streefkerk et al, 2009). In effect, an automated task allocation system provides the optimal distribution of incidents among available team members.…”
Section: Benefits and Costs Of Task Allocationmentioning
confidence: 98%
See 3 more Smart Citations